Application and Properties of Nano‐sized RDX in CMDB Propellant with Low Solid Content. Issue 2 (30th November 2017) - Liu, Jie; Ke, Xiang; Xiao, Lei; Hao, Gazi; Rong, Yuanbo; Jin, Chengsu; Jiang, Wei; Li, Fengsheng
Abstract: Composite modified double‐base (CMDB) propellant, benefitting from the outstanding performances of high energy and low signature, has attracted increasing focus in the past decade. To improve the integrative performance, such as enhancing the mechanical property and decreasing the sensitivity, CMDB propellant with low solid content containing nano‐sized RDX has been prepared. The microstructure, mechanical properties, sensitivity and combustion performance of the prepared propellant are studied. Results have shown that the interface of the CMDB propellant contained nano‐sized RDX (N‐CMDB) is more compact and the internal defects are less than those of the CMDB propellant with micro‐sized RDX (M‐CMDB). Compared with the maximum tensile strength ( σm ) and the corresponding elongation at maximum tensile strength ( ϵm ) of M‐CMDB, the σm values of N‐CMDB are improved by 37.4 % at +50 °C, 27.5 % at +20 °C and 26.7 % at −40 °C, and the ϵm values are increased by 16.1 %, 19.4 % and 39.6 %, separately. Moreover, the friction and impact sensitivities of N‐CMDB propellant are decreased by 51.3 % and 50.4 %, respectively. In the range of 8–18 MPa, the combustion performance of N‐MCDB propellant has been demonstrated more attractive with higher burning rate coefficient (8.692→10.950) and lower pressure exponent (0.384→0.299). All these results lead us to believe that the usage of nano‐sized explosives will contribute to improve the comprehensive performance of CMDB propellants and promote their application in weapon system. Abstract :